2018
DOI: 10.1523/eneuro.0038-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

RNA from TrainedAplysiaCan Induce an Epigenetic Engram for Long-Term Sensitization in UntrainedAplysia

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 65 publications
3
51
0
Order By: Relevance
“…As with the Queenan et al (2017) study suggesting that LTP is not mediated by persistent synaptic changes, a similar suggestion has been made for some forms of learning in Aplysia. Chen et al (2014) and Bedecarrats et al (2018) claim that the synaptic changes investigated in detail in Aplysia are an epiphenomenon of cellular changes at the cell body, and that learning can be transferred by RNA from trained to untrained animals (this revives the 1960′s ideas of McConnell who suggested learning transfer by RNA in flatworms (see Smalheiser et al 2001;Rilling 1996).…”
Section: Examples Of Psychoneural Reduction-the Cellular Basis Of Memorymentioning
confidence: 97%
See 1 more Smart Citation
“…As with the Queenan et al (2017) study suggesting that LTP is not mediated by persistent synaptic changes, a similar suggestion has been made for some forms of learning in Aplysia. Chen et al (2014) and Bedecarrats et al (2018) claim that the synaptic changes investigated in detail in Aplysia are an epiphenomenon of cellular changes at the cell body, and that learning can be transferred by RNA from trained to untrained animals (this revives the 1960′s ideas of McConnell who suggested learning transfer by RNA in flatworms (see Smalheiser et al 2001;Rilling 1996).…”
Section: Examples Of Psychoneural Reduction-the Cellular Basis Of Memorymentioning
confidence: 97%
“…Requirements for explaining circuit function have been outlined by scientists (e.g. Yuste 2008; Koch 2012; Braganza and Beck 2018) and philosophers (Bechtel and Richardson 1993;Bechtel 2008;Machamer et al 2000;Silva and Bickle 2009; Piccinini and Craver 2011; Craver and Kaplan 2018). These outlines repeat but don't refer to criteria previously applied to neurophysiological analyses of invertebrate and lower vertebrate model systems (Bullock 1976;Selverston 1980;Getting 1989).…”
Section: Metascientific Approachmentioning
confidence: 99%
“…In addition to Trettenbrein’s ( 2016 ) critique, models of learning and memory based on non-synaptic plasticity have been proposed (Mozzachiodi and Byrne, 2010 ; Cacha et al, 2017 ), but these appear to involve neuromodulatory actions which alter the parameters of LTP and LTD, and thus the efficacy of synaptic plasticity. In addition, Arshavsky ( 2006 , 2017 ), Chen et al ( 2014 ) and Bèdècarrats et al ( 2018 ) have advocated a genomic rather than a synaptic theory of memory and argue that changes in individual neurons rather than interconnected neural networks form the basis of memory. Bèdècarrats et al ( 2018 ) demonstrated that the transfer of RNA from trained to naïve animals is sufficient to induce behavioral correlates of memory and that these changes are dependent on DNA methylation.…”
Section: Reconciliation Of the Differences Between Physiologists And mentioning
confidence: 99%
“…In addition, Arshavsky ( 2006 , 2017 ), Chen et al ( 2014 ) and Bèdècarrats et al ( 2018 ) have advocated a genomic rather than a synaptic theory of memory and argue that changes in individual neurons rather than interconnected neural networks form the basis of memory. Bèdècarrats et al ( 2018 ) demonstrated that the transfer of RNA from trained to naïve animals is sufficient to induce behavioral correlates of memory and that these changes are dependent on DNA methylation. However, the modified expression of these gene products likely serves to change synaptic weights, an idea supported by Bèdècarrats et al’s ( 2018 ) demonstration of an increase in sensory neuron excitability following RNA injection.…”
Section: Reconciliation Of the Differences Between Physiologists And mentioning
confidence: 99%
“…Secondly, the dynamical processes related to memory dynamics are governed by biochemical processes, such as protein networks and chromatin modifications. Some of these processes take part as the neural and molecular basis of behavior, in addition to learning (25)(26)(27)(28)(29) . Thirdly, neurons interact by exploiting dozens of neuromodulators, neuropeptides, diffusible molecules, hormones and RNA, whose effect is not restricted to learning (30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41) .…”
Section: Introductionmentioning
confidence: 99%